Spontaneous thought and early Chinese ideas of 'non-action' and 'emotion'. - Eifring, Halvor (Asian Philosophy, 2019)
The early Chinese idea of non-action refers not to spontaneity, as has been argued, but to a relation between agency and spontaneity. Non-action needs to be seen in connection with the idea of emotion, which refers to the spontaneity involved. The debates surrounding non-action and emotion can be profitably compared to discussions of spontaneous thought in modern cognitive science. Early Chinese approaches supplement modern ideas by focusing on feelings rather than thought and by being more relational and ecological, seeing agency and spontaneity as parallel processes in constant interaction rather than mutually exclusive categories. Furthermore, emotions represent an inner counterpart to the external changes in our physical and social environment, pointing to a close connection between the nature within us and outside us. On a larger scale, therefore, non-action denotes a relation between deliberate action and the given internal and external situation within which such action takes place.